Literature of Drama in Arabic World: https://doi.org/10.5281/zenodo.17043529 - Prof. Dr. Matloob Ahmad; Dr. Mufti Muhammad Saleem; Dr. Anum Hamid (Corresponding Author) (`, 2025)
The research, entitled “Literature of drama in Arabic World” This research study is treated differs in the two topics, while in the first it is drama in Arabic prase, and in the second it is in the poetry. The world has witnessed a comprehensive scientific renaissonce during the last century. With Egypt and Lebnon at the forefront. While other neighboring countries lagged behind. The Kingdom of Saudi Arabia contributed to this delay, and a large number of modern schools, colleges and universities were estabilshed throughout them, as well as private schools and colleges for girls. Scientific missions were also sent Egypt and other countries. The Saudi government also did every thing in its power to support this comprehensive renaissance. As for drama literature and theatre begun in Lebanon with Maroun Al Naqqash’s Play. As well as in the other words. Poetic theatre is one of the most influential literary arts, and it contains all the artistic elements that should be present in a poetic novel. Keyword: Drama, World, Poetry, Novel, Theater, Arabic, Prase.